Reductive Metabolism Influences the Toxicity and Pharmacokinetics of the Hypoxia-Targeted Benzotriazine Di-Oxide Anticancer Agent SN30000 in Mice - Gu, Yongchuan; Chang, Tony T.-A.; Wang, Jingli; Jaiswal, Jagdish K.; Edwards, David; Downes, Noel J.; Liyanage, H. D. Sarath; Lynch, Courtney R. H.; Pruijn, Frederik B.; Hickey, Anthony J. R.; Hay, Michael P.; Wilson, William R.; et al. (Frontiers in Pharmacology, 2017)
3-(3-Morpholinopropyl)-7,8-dihydro-6H-indeno[5,6-e][1,2,4]triazine 1,4-dioxide (SN30000), an analogue of the well-studied bioreductive prodrug tirapazamine (TPZ), has improved activity against hypoxic cells in tumour xenografts. However, little is known about its biotransformation in normal tissues. Here, we evaluate implications of biotransformation of SN30000 for its toxicokinetics in NIH-III mice. The metabolite profile demonstrated reduction to the 1-N-oxide (M14), oxidation of the morpholine side-chain (predominantly to the alkanoic acid M18) and chromophore, and subsequent glucuronidation. Plasma pharmacokinetics of SN30000 and its reduced metabolites was unaffected by the presence of HT29 tumour xenografts, indicating extensive reduction in normal tissues. This bioreductive metabolism, as modelled by hepatic S9 preparations, was strongly inhibited by oxygen indicating that it proceeds via the one-electron (radical) intermediate previously implicated in induction of DNA double strand breaks and cytotoxicity by SN30000. Plasma pharmacokinetics of SN30000 and M14 (but not M18) corresponded closely to the timing of reversible acute clinical signs (reduced mobility) and marked hypothermia (rectal temperature drop of ~ 8oC at nadir following the maximum tolerated dose). Similar acute toxicity was elicited by dosing with TPZ or M14, although M14 did not induce the kidney and lung histopathology caused by SN30000. M14 also lacked antiproliferative potency in hypoxic cell cultures. In addition M14 showed much slower redox cycling than SN30000 in oxic cultures. Thus a non-bioreductive mechanism. mediated through M14, appears to be responsible for the acute toxicity of SN30000 while late toxicities are consistent with DNA damage resulting from its one-electron reduction. A two-compartment pharmacokinetic model, in which clearance of SN30000 is determined by temperature-dependent bioreductive metabolism to M14, was shown to describe the non-linear PK of SN30000 in mice. This study demonstrates the importance of non-tumour bioreductive metabolism in the toxicology and pharmacokinetics of benzotriazine di-oxides designed to target tumour hypoxia.